TEKNOLOGI PAKAN SILASE DAN FERMENTASI UNTUK PERBAIKAN USAHA PETERNAKAN SAPI DI DESA PADANG CAKUR KOTA PARIAMAN - Ediset Ediset; Imana Martaguri; Amrizal Anas; Ida Indrayani; Yona Resila Foci; Fadhli Ilhami Khairi (Jurnal Hilirisasi IPTEKS, 2023)
Padang Cakur Village, South Pariaman Subdistrict, Pariaman City, holds potential for the development of cattle farming. However, local cattle farmers are facing challenges in meeting the feed requirements due to shrinking green pasturelands. To address this issue, alternative feed sources from agricultural waste are needed. The problem lies in the fact that farmers lack the knowledge and skills to process agricultural waste into cattle feed. This technology transfer activity aims to: 1) Enhance the knowledge and skills of cattle farmers in utilizing agricultural waste, such as rice straw fermentation with the addition of sago (Silage), as cattle feed, and 2) Improve cattle farmers' understanding of the process of fermenting banana stems with the addition of rice bran. The methods employed in this technology transfer activity include extension through lectures and training sessions. Lecture-based methods are used to deliver information regarding both feed technologies, while training sessions are conducted to demonstrate the procedures for producing rice straw silage with sago and fermenting banana stems with rice bran. The outcomes of this technology transfer activity have increased the knowledge and skills of cattle farmers, particularly in feed production technologies like rice straw silage with sago (Silage) and fermented banana stem feed with rice bran. As evidence of success, participating cattle farmers have collectively produced 50 kilograms of Silage and 30 kilograms of fermented banana stem feed.